Kathy Griffin's celebrity run-ins : (my A-Z index) - Griffin, Kathy, 1960- (Flatiron Books, 2016)
An A-Z compendium of the celebrities comedian and TV personality Kathy Griffin has met over the years and the anecdotes only she can tell about them.